Crude palm oil clarification by three phase decanting centrifuge, steady and dynamic state modeling - Sulong, Mohamad; Abdul Aziz, Mustafa Kamal (1989)

(untitled)
The quality control performance of the three phase decanting centrifuge was determined using statistical process control techniques. Individual X-charts of feed component: oil, water and solid indicated that these inputs were tending towards positive instability resulting in an overall fourth order polynomial time instability of the oil light phase and decreasing oil composition in the light, heavy, and solid phases. This confirms that the settling tank performance was highly variable causing severe quality controls deviations in the centrifuge outputs. Theses disturbances are then transmitted via the output streams to the adjoining units such as sludge tank, oil tank and eventually to the separators. This is in contrast with the role of the settling tank which is to compact the solids and to buffer out outflow deviations.